PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS KETERAMPILAN BERPIKIR TINGKAT TINGGI PADA PEMBELAJARAN TEMATIK - Serma Ulipa Simbolon (EJoES (Educational Journal of Elementary School), 2021)
The development of students' worksheets based on high level skills was motivated by the thematic learning carried out as well as the use of LKPD only to develop and test memory and memorize onl  The purpose of this study is to develop a Student Worksheet (LKPD) based on high-level thinking skills to be suitable for use by fifth grade elementary school students, and effectively improve students' critical thinking skills in thematic learning. This research is a development study using the Borg and Gall model. The subjects of this study were fifth grade students at SD Negeri 040460 Berastagi. The instruments used were expert validation questionnaire and achievement test. The results showed: (1) based on the results of expert validation, it was found that LKPD was based on high level skills for fifth grade students with an average validation score of 93% or a very valid category; (2) based on the results of field trials it has been found that LKPD based on high-level thinking skills on the concept of human and animal motion organs can effectively improve students' ability to think critically in thematic learning in class V. Improvements are seen in the value of the gain obtained to reach a score of 83 at small group trials and a score of 80 in large groups that are categorized as "High".